Análisis del encanutado de bocachico como plato típico representativo de la Provincia de Los Ríos - Rendon Franco, Tais Argentina (2022)
This research work aims to analyze the encanutado de bocachico as a typical representative dish of the province of Los Ríos, with the purpose of determining the cultures, customs and ancestral traditions reflected in the cultural tourism. The gathering of information to identify if the "encanutado de bocachico" is representative, specifying the problem statement, the justifications of the research, the general and specific objectives, all these focused on the gastronomic representativeness with the purpose of developing a theoretical foundation, describing the current situation, general information, important data, rediscovering its gastronomic culture. It was generated through descriptive research, with qualitative methodology and bibliographic and historical-logical methods, applying the triangulation of data that will allow the collection of information from the case study. The survey yielded adequate results for the execution of the project, allowing us to develop the research, once the information was collected, the respective analysis of the results was carried out. The recommendations to strengthen the "encanutado" of bocachico, a typical dish of the canton of Mocache, are detailed.